Sustainability index with integrated indicator dependencies - Wagenhals, Sabine; Garner, Wendy; Duckers, Les; Kuhn, Katja (Business, Management and Economics Engineering, 2014)
Sustainability is a growing concern worldwide. While companies used to focus on financial performance, now the focus has shifted to considering envi- ronmental and social performance as well. This trend is not only based on ‘image’, but recent research has proven that a complex approach regarding sustainability could significantly increase a company’s performance. The selection of sustainability indicators as well as the development of sustainabil- ity frameworks has been analysed by researchers already. The authors argue that interdependencies exist between different sustainability indicators and concepts. To address this issue, the fuzzy set method has been used and integrated into as- sessment methods, making it possible to develop a sustainability index which is able to consider the dependencies of the integrated variables. The proposed method can prove that indicator dependencies have a significant influence on the sustain - ability performance of a company and therefore on its overall performance.